13th International IEEE Conference on Intelligent Transportation Systems 2010
DOI: 10.1109/itsc.2010.5625028
|View full text |Cite
|
Sign up to set email alerts
|

Reconstruction of delay distribution at signalized intersections based on traffic measurements

Abstract: In an urban road network, travel times are not uniquely determined by the traffic states due to stochastic properties of traffic flow, stochastic arrivals and departures at intersections and traffic signal control. As a result, for a given traffic state, a range of travel times (delays) is found. This can be represented by a distribution of travel times (delays). Calibrating a model for the travel time only for the expectation value gives a large 'noise' such that the model will have little value for the predi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 19 publications
0
3
0
Order By: Relevance
“…Zheng and Van Zuylen [19] indicated that the parameters of a delay distribution could be properly estimated for both undersaturated and oversaturated intersections using the trajectories of vehicles. They used delay distribution functions at intersections (Equations (2) and (3)) to determine the parameters of the dynamic model of the traffic at intersections.…”
Section: Parameter Estimationmentioning
confidence: 99%
“…Zheng and Van Zuylen [19] indicated that the parameters of a delay distribution could be properly estimated for both undersaturated and oversaturated intersections using the trajectories of vehicles. They used delay distribution functions at intersections (Equations (2) and (3)) to determine the parameters of the dynamic model of the traffic at intersections.…”
Section: Parameter Estimationmentioning
confidence: 99%
“…Derivation of these algorithms is usually accompanied with some fundamental assumptions, e.g., no lanechanging and/or known arrival distribution(s), which restrict their practicality. The data-driven algorithms, however, largely rely on fitting a significant amount of data with well-established probability distributions (Hofleitner, Herring, & Bayen, 2012a;Uno, Kurauchi, Tamura, & Iida, 2009;Zheng & van Zuylen, 2010). The major issue is the availability of enough data for model training.…”
Section: Introductionmentioning
confidence: 99%
“…At present, there are two general trends in estimation of travel times using this probe data. One trend, from kinematic wave theory (see [18,7]), derives analytical probability distributions of travel times and infer their parameters with probe vehicle data. These approaches are computationally intensive, which limits their applicability for large scale networks.…”
Section: Introductionmentioning
confidence: 99%